HUBUNGAN POLA ASUH ORANGTUA DAN KEMANDIRIAN ANAK - Kustiah Sunarty (Universitas Negeri Makassar, 2016)
This study examines patterns of parenting and the child's self reliance. The research problem is whether there is a relationship between parenting parents and the child's self reliance? The research questions: (1) which type of parenting is now used parents in an effort to increase the child's self reliance? (2) Which type of parenting that can increase the child's self reliance? (3) Is there a relationship between parenting parents and the child's self reliance? The purpose of research is to determine: (1) the type of parenting parents present in order to increase the child's self reliance, (2) the type of parenting can increase the child's self reliance, (3) the relationship between parenting parents and the child's self reliance. The study population is the students of Junior High School in the city of Makassar. Data were collected through scale/questionnaire. Data were analyzed with descriptive statistics and inferential statistics. The results showed that: (1) the type of parenting parents used today to improve their self-reliance, respectively: positive parenting, democratic, authoritarian, permissive, negative/ unhealthy, and neglectful; (2) positive parenting and democratic can increase the child's self reliance, and 3) there is a positive and significant relationship between parenting parents and the child's self reliance.